1979
DOI: 10.1136/thx.34.5.637
|View full text |Cite
|
Sign up to set email alerts
|

Lung distensibility and airway function in intermediate alpha 1-antitrypsin deficiency (Pi MZ).

Abstract: (-) and it is not possible to distinguish between MM and M-subjects or ZZ and Z-subjects by Pi typing. The vast majority of Pi M subjects will be homozygotes (Pi MM) (First International Workshop on the Pi system, 1975).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

1980
1980
2003
2003

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…As several authors [23,31,34,36] have repeatedly pointed out, the simpler tests cannot, in all cases, accurately discriminate between PiMZ and PiMM individuals. It is well-known that asymptomatic individuals showing normal conventional tests of pulmonary function may have significant degrees of mechanical abnormality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As several authors [23,31,34,36] have repeatedly pointed out, the simpler tests cannot, in all cases, accurately discriminate between PiMZ and PiMM individuals. It is well-known that asymptomatic individuals showing normal conventional tests of pulmonary function may have significant degrees of mechanical abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Large surveys of various populations (from a community or from a working population) have been analysed to identify persons with intermediate deficiency, and to compare their respiratory status to control groups with the normal MM type selected from the same population; in some studies, matched-pairs were used [5,8,9,[15][16][17][18][19][20][21][22][23]. Other cross-sectional studies have addressed the question of whether the prevalence of heterozygotes among patients with emphysema or related disease is higher than among control populations [6,7,19,22,[24][25][26][27][28][29].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, both of these studies used relatives in the MZ study population and, therefore, the results may not be due to mutations in the α 1 -AT gene. TATTERSALL et al [59] found evidence for greater loss of elastic recoil in MZ versus MM smokers, but estimates of airway function were similar in both groups. HALL et al [60] found that MZ heterozygotes had significantly lower expiratory flow rates, even in the absence of smoking.…”
Section: Alpha 1 -Antitrypsinmentioning
confidence: 96%
“…These studies, however, are not without limitations and it has been proposed that Pi-MZ patients self-select away from exposures that would result in impaired pulmonary physiology (156). Other studies have revealed subtle abnormalities of pulmonary function in association with the Pi-MZ genotype, including alterations in pressure/volume curves (157).…”
Section: Definition and Pathophysiology Of Copdmentioning
confidence: 99%